Inhibition of renal fibrosis with a human CXCL9‐derived glycosaminoglycan‐binding peptide. Issue 2 (2nd February 2022) - Poosti, Fariba; Soebadi, Mohammad Ayodhia; Crijns, Helena; De Zutter, Alexandra; Metzemaekers, Mieke; Berghmans, Nele; Vanheule, Vincent; Albersen, Maarten; Opdenakker, Ghislain; Van Damme, Jo; Sprangers, Ben; Proost, Paul; et al.
Abstract: Objectives: Renal fibrosis accompanies all chronic kidney disorders, ultimately leading to end‐stage kidney disease and the need for dialysis or even renal replacement. As such, renal fibrosis poses a major threat to global health and the search for effective therapeutic strategies to prevent or treat fibrosis is highly needed. We evaluated the applicability of a highly positively charged human peptide derived from the COOH‐terminal domain of the chemokine CXCL9, namely CXCL9(74–103), for therapeutic intervention. Because of its high density of net positive charges at physiological pH, CXCL9(74–103) competes with full‐length chemokines for glycosaminoglycan (GAG) binding. Consequently, CXCL9(74–103) prevents recruitment of inflammatory leucocytes to sites of inflammation. Methods: CXCL9(74–103) was chemically synthesised and tested in vitro for anti‐fibrotic properties on human fibroblasts and in vivo in the unilateral ureteral obstruction (UUO) mouse model. Results: CXCL9(74–103) significantly reduced the mRNA and/or protein expression of connective tissue growth factor (CTGF), alpha‐smooth muscle actin (α‐SMA) and collagen III by transforming growth factor (TGF)‐β1‐stimulated human fibroblasts. In addition, administration of CXCL9(74–103) inhibited fibroblast migration towards platelet‐derived growth factor (PDGF), without affecting cell viability. In the UUO model, CXCL9(74–103) treatment significantly decreased renal α‐SMA, vimentin, and fibronectin mRNA and protein expression. Compared with vehicle, CXCL9(74–103) attenuated mRNA expression of TGF‐β1 and the inflammatory markers/mediators MMP‐9, F4/80, CCL2, IL‐6 and TNF‐α. Finally, CXCL9(74–103) treatment resulted in reduced influx of leucocytes in the UUO model and preserved tubular morphology. The anti‐fibrotic and anti‐inflammatory effects of CXCL9(74–103) were mediated by competition with chemokines and growth factors for GAG binding. Conclusions: Our findings provide a scientific rationale for targeting GAG–protein interactions in renal fibrotic disease. Abstract : Fibrosis is an important clinical problem for which no optimal therapy is available. We evaluated the therapeutic use of a human CXCL9‐derived peptide, 'CXCL9(74–103)', which is a stronger glycosaminoglycan (GAG) binder than most full‐length chemokines to reduce fibrosis. Our findings demonstrate the potential therapeutic effect of targeting GAG coreceptor functions in diminishing inflammation and fibrogenesis. Consequently, in addition to antagonists of the GPCRs activated by chemokines, targeting GAG interactions provides an alternative strategy to control chemokine‐mediated inflammation and fibrosis.